Realizing universal quantum gates with topological bases in quantum-simulated superconducting chains - Yong Hu (Nature Portfolio, 2017)
Superconducting circuit quantum simulator of time-reversal-invariant topological superconductors Topological quantum matters have been recognized to have promising applications in realizing novel fault-tolerant quantum processes. In particular, one-dimensional time-reversal-symmetric (TRS) topological superconductors may be utilized to establish universal quantum gates with topological bases. However, how to realize them in conventional electronic systems is extremely challeging due to constraints of materials and coexisting complicated mechanisms. Here Hu, Zhao, Xue, and Wang propose an experimentally feasible scheme of hard-core boson quantum-simulator of such spinful TRS topological superconductors. Using a dispersive dynamic modulation approach, not only a faithful quantum simulation of TRS superconductor is achieved, but also a set of universal quantum gates can be constructed topologically. Physical implementation of this scheme is also elaborated based on superconducting quantum circuits, reavealing its feasibility with current technology.